An Uncommon Complication of Multiple Myeloma in a Post Bone Marrow Transplant patient–Plasma Cell Pleocytosis - Prachi; Sharma Gaurav (Journal of Body Fluids, 2022)
This case report describes plasma cell pleocytosis occurring after bone marrow transplantation for multiple myeloma. The authors outline clinical presentation, cerebrospinal fluid findings, and differential diagnosis, emphasizing the need to consider hematologic relapse or CNS involvement in post‑transplant patients with neurologic symptoms. Management considerations and follow‑up strategies are discussed.
Keywords: Plasma cell pleocytosis